Effectiveness of conference feedback on college students’ composition in the English as a Second Language (ESL) context - Thambirajah, Jeremy Ivan; Noordin, Nooreen (International Institute for Science, Technology & Education, 2014)
This article examines the negotiation teacher-student feedback conferences in a college writing course. The conferences were held in groups with one teacher and six participants who agreed to take part in this study. The study includes the right for the teacher to offer advice and to criticize, which is often considered to be threatening in more normal contexts. However, as the data analysis shows, participants also interact in ways that challenge the common norms, some of which might be considered more conventionally attacking. The article argues that conference feedback should be analyzed at the level of interaction (Haugh and Bargiela-Chiappini, 2010) and that situated and contextual detail is relevant to its analysis. The study suggests that teachers’ in a second language writing classroom should provide conference feedback so that student understand what the teachers’ expect of them and, provides a useful theoretical framework for doing so. The conclusion of the study draws on real-life talk-in-interaction (from transcribed recordings), the participants’ perspectives (from focus groups and interviews) and situated detail (from field-notes) to produce a contextualized and nuanced analysis.